2019
DOI: 10.5210/fm.v24i5.9473
|View full text |Cite
|
Sign up to set email alerts
|

Exploring and analyzing the dark Web: A new alchemy

Abstract: The Tor network is an encrypted network that allows anonymous access to the Internet for its users. The Tor network also hosts hidden services which constitute the infamous dark Web. These hidden services are used to carry out activities that are otherwise illegal and unethical on the surface Web. These activities include distribution of child pornography, access to illegal drugs, and the sale of weapons. While Tor hidden services provide a platform for uncensored ventures and a free expression of thoughts, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…In contrast, while the majority of hosted Onion/Hidden Services are often not per se illegal ( 28 , 30 ), user demand for this content tends to suggest that illicit use of Onion/Hidden Services predominates ( 6 ). First, one 2015 study investigating site visits to Onion/Hidden Services found that roughly 82% of requests over a 6-month observation period went to child abuse imagery sites, although this period also corresponded with a major FBI investigation into the Playpen child abuse imagery site ( 7 ).…”
Section: Data Material and Methodsmentioning
confidence: 99%
“…In contrast, while the majority of hosted Onion/Hidden Services are often not per se illegal ( 28 , 30 ), user demand for this content tends to suggest that illicit use of Onion/Hidden Services predominates ( 6 ). First, one 2015 study investigating site visits to Onion/Hidden Services found that roughly 82% of requests over a 6-month observation period went to child abuse imagery sites, although this period also corresponded with a major FBI investigation into the Playpen child abuse imagery site ( 7 ).…”
Section: Data Material and Methodsmentioning
confidence: 99%
“…Third, the Dark Web has a wide variety of functions, many of which do not involve drugs at all and are in fact not even illegal within the United States. Categorizations of available Darknet .onion hidden services have consistently found large volumes of legal content on the Tor-hosted Dark Web (Faizan & Khan, 2019;Moore & Rid, 2016;Owen & Savage, 2015), which also mirrors studies of single Dark Web social networking sites (Gehl, 2016(Gehl, , 2018. Indeed, increased political repression correlates with actual Tor usage rates at a national level, suggesting that the Dark Web is a powerful tool of rights-based expression (Jardine, 2018b).…”
Section: Limitationsmentioning
confidence: 85%
“…Research papers N. of papers Content classification [23], [24], [25], [26], [9], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38] 17…”
Section: Research Fieldmentioning
confidence: 99%
“…In contrast, Savage and Owen [32] return to manual study and classification, suggesting that given the variety and complex technical nature of some content, automatic classifiers would be insufficient, due to the difficulty of interpreting the context completely. Other documentation of a manual classification reviewing 3480 HS is by Faizan and Khan [28], but they claim that only 38% of the servers found offer illegal services.…”
Section: Content Classificationmentioning
confidence: 99%